Management optimisation of water distribution systems: the TILDE project (Tool for Integrated Leakage Detection) - Fantozzi M.; Pretner A.; Marshallsay D. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The TILDE project is aimed at optimising the performance of public water supply networks by controlling water losses. TILDE focuses on developing tools that will advance the state of the art in leakage management. The TILDE Decision Support Tool (DST) will guide water utilities in the process of operating their water networks and programming their investments. The TILDE DST will be developed to provide end-users with solutions tailored to their specific needs whilst ensuring its applicability to other potential users throughout Europe, or even worldwide. The TILDE DST will help to supply customers with a better water service; it will contribute to save water that is currently wasted, and it will optimise the cost benefit ratio of the investments planned. The TILDE Web Portal aims at disseminating Best Practice on water distribution at a European wide scale.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)